Esoteeristen naisten lumottu toimijuus - Tiina Mahlamäki; Terhi Utriainen (Teologinen julkaisuseura, 2022)
Enchanted Agency among Finnish Esoteric Women — This article traces and explores esoteric agency among Finnish women, understanding agency as the capacity for a subject to make meaningful differences in her lifeworld, which consists of relations with the this-worldly and sometimes also the otherworldly. The article analyses the esoteric factors and features in the life, first, of the Anthroposophist and writer Kerstin Bergroth (1886–1975) and, second, of Finnish women in the present who have developed an interest in angel spirituality. Our analysis draws from scholarship on Western Esotericism in identifying how Finnish women from different generations enact participatory and even enchanted agency in the often complex spaces where secular society, Lutheran culture, and esoteric influences and worldviews coexist.